Decreased low-frequency amplitude of the right caudate nucleus in patients with chronic schizophrenia treated with risperidone combined with clozapine - Chen, Xinyue; Lei, Lixing; Li, Hangyu; Li, Ying; Peng, Shiji; Liao, Kaike; Yu, Rui; Liu, Nian (Frontiers in Psychiatry, 2025)
BackgoundWhile risperidone and clozapine monotherapies have been linked to distinct neuroimaging profiles in chronic schizophrenia, the combined effects of these treatments on brain function remain unclear. This study aimed to compare spontaneous neural activity between patients receiving risperidone monotherapy and those undergoing risperidone-clozapine combination therapy, and to investigate how these neural alterations relate to clinical symptomatology.MethodsThis study enrolled 28 patients with chronic schizophrenia who had been treated with long-term risperidone monotherapy (RT-SZ), 40 patients receiving long-term combination therapy with risperidone and clozapine (RCT-SZ), and 30 healthy controls (HCs) comparable in sex, age, and educational level. Resting-state functional magnetic resonance imaging (rs-fMRI) was utilized for acquiring neural data, and amplitude of low-frequency fluctuation (ALFF) was computed to examine activity in different brain regions. Group comparisons were conducted using analyses of covariance (ANCOVAs) with age, sex, and educational level as covariates, followed by post-hoc testing. Partial correlation analyses were performed to examine associations between ALFF alterations and clinical symptoms or cognitive performance.ResultsBoth the RT-SZ and RCT-SZ groups exhibited significantly reduced ALFF in the bilateral lingual gyrus and right middle occipital gyrus, along with raised ALFF in the right caudate nucleus and right medial superior frontal gyrus, relative to HCs. Additionally, the RT-SZ group showed elevated ALFF in the left caudate nucleus, while the RCT-SZ group demonstrated decreased ALFF in the left postcentral gyrus. Notably, the RCT-SZ group exhibited reduced ALFF in the right caudate nucleus compared to the RT-SZ group. Partial correlation analysis revealed a positive trend between ALFF in the left lingual gyrus and measures of attention and information processing speed among chronic schizophrenia patients.ConclusionsThis exploratory analysis observed a more pronounced decrease in right caudate nucleus ALFF in the combination therapy group compared to the risperidone monotherapy group. The observed differences in neural activity patterns provide preliminary neuroimaging clues suggesting potential distinct neural effects between long-term monotherapy and combination therapy in chronic schizophrenia, and may offer new directions for exploring neuroimaging explanations for the combination therapy.